Digital Transformation in Public Services: A Study of E-Government Implementation in Indonesia - Syafaruddin Syafaruddin; Andi Riska Andreani S (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
Digital transformation has fundamentally reshaped the landscape of public service delivery worldwide, with e-government emerging as a critical mechanism for enhancing government efficiency, transparency, and citizen engagement. This article provides a comprehensive analysis of e-government implementation in Indonesia, examining the trajectory of digital transformation in public services, the institutional frameworks supporting this transition, and the multifaceted impacts on service quality and governance outcomes. Through systematic literature review and critical policy analysis, this research explores the evolution of Indonesia's e-government initiatives from early adoption to current comprehensive digital service platforms, investigating both successes and persistent challenges. The findings reveal that Indonesia has made substantial progress in developing e-government infrastructure and applications across national and local government levels, with notable achievements including integrated digital identity systems, online business licensing platforms, and citizen complaint management systems. These initiatives have demonstrably improved service accessibility, reduced processing times, minimized corruption opportunities, and enhanced government responsiveness. However, implementation remains uneven across regions and government institutions, constrained by factors including digital infrastructure disparities, limited digital literacy among citizens and officials, organizational resistance to change, inadequate interoperability between systems, and cybersecurity vulnerabilities. The research identifies critical success factors for effective e-government implementation including strong leadership commitment, adequate resource allocation, comprehensive capacity building programs, citizen-centric design principles, robust legal frameworks, and collaborative partnerships between government, private sector, and civil society.